Understanding Mainland Chinese Tourists' Motivation and Constraints of Visiting Taiwan. Issue 3 (1st October 2016) - Song, Hanqun; Liu, Kuo-Ning; Huang, Yu-Ting
ABSTRACT: China has been by far the fastest growing source market in recent years and is now the largest tourism source market in the world. Mainland Chinese travelers were permitted to directly visit Taiwan in 2008. Within a short period of time, the Mainland Chinese travel market has become the top source market for Taiwan's tourism industry. However, limited attention has been paid to the travel behavior of this significant market, such as why Mainland Chinese travelers visit Taiwan and why do they not. Using interviews, this study identified a list of motivation factors and travel constraint factors. Three themes, intrapersonal, interpersonal, and contextual factors, influenced Mainland Chinese tourists' intention to visit Taiwan. In particular, contextual factors, such as 'the cross-strait relations' between Mainland China and Taiwan, play a key role in influencing tourists' visit intention. Like two sides of the same coin, 'the cross-strait relations' could be a facilitator to attract Mainland Chinese tourists or an inhibitor to stop Mainland Chinese visiting Taiwan.